Laboratory results and clinical findings of children with hydatid cyst disease - Tartar, T.; Bakal, U.; Sarac, M.; Kazez, A. (Wolters Kluwer Medknow Publications, 2020)
Objectives: The relationship hydatid cyst (HC) is a parasitic disease that is endemic worldwide. Aims: To study the clinical findings and laboratory results of patients with hydatid disease. Materials and Methods: Total number of patients (n = 78) who underwent surgery for HC disease from 2000 to 2017 were retrospectively evaluated. The patients' demographic characteristics, reasons for admission into hospital, lesion location and size, laboratory results, and complications were recorded. Results: Of the HCs, 59% and 26.9% were located in the liver and lungs, respectively. The rate of multiple organ involvement was 10.3%. A total of 16 (20.5%) cases had ruptured HCs (7 livers, 7 lungs, 1 spleen, and 1 omentum). There was no significant difference in the rate of eosinophilia between patients with and without cyst rupture (P = 0.9). Indirect hemagglutination (IHA) tests yielded negative results in 38.9% of the patients; among them, 32.1% had ruptured HCs. A negative IHA test result was significantly associated with rupture (P = 0.046). No significant difference between rupture and cyst size or location was found. Conclusions: HC rupture was not correlated with cyst size. The sensitivity of serological tests and the blood eosinophil count was low, even in cases of ruptured HCs. The recurrence rate can be reduced by open surgery and medical treatments.
Keywords: Child; echinococcosis; hemagglutination test; recurrence; rupture